2013
DOI: 10.1007/s11258-013-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Artefacts of the pot environment on soil nutrient availability: implications for the interpretation of ecological studies

Abstract: Pot experiments are frequently used to examine plant, soil, and microbial interactions that cannot be studied in situ. Although impacts of the pot environment on seedling growth have long been recognized, they are rarely addressed directly in current ecological studies. Here we examine how commonly used soil conditioners, often necessary to maintain adequate drainage in pots, can influence nutrient availability and seedling growth. Balsawood (Ochroma pyramidalis) seedlings were grown in central Panama in soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…, but was reduced by the addition of the rice husks (Dalling et al, 2013), counteracting the observation of excess N mineralization observed in un-amended soils (e.g. Johnson et al, 1995;Ross and Hales, 2003).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…, but was reduced by the addition of the rice husks (Dalling et al, 2013), counteracting the observation of excess N mineralization observed in un-amended soils (e.g. Johnson et al, 1995;Ross and Hales, 2003).…”
mentioning
confidence: 80%
“…Soil was air-dried ($27 C) and passed through a 10-mm sieve. Details of the soil used in the experiment and its analysis are described in Dalling et al (2013). Briefly, the soil has a high concentration of exchangeable phosphate (17Á8 mg P kg À1 ), based on extraction from anion exchange membranes, and a high effective cation exchange capacity (53Á2 cmol c kg…”
Section: Seedling Growth Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…,b, Dalling et al. ). All shoot and root material was removed separately for each plant, dried (60°C, 72 h) and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Oftentimes, pot experiments are used to estimate the strength of plantplant interactions and to establish the dominance hierarchy of different species. Pot experiments provide better control than experiments in the field, but they can be plagued by artefacts caused by the limited pot volumes (de Kroon 2007) or unrealistic physicochemical properties of the substrate (Passioura 2006;Dalling et al 2013). Taken together, previous research suggests that substrate should be taken into account when testing for plant competition with pot experiments.…”
Section: Introductionmentioning
confidence: 99%